Probing electronic structure of stoichiometric and defective Sn O2 - Moreno, Mario Sergio Jesus (2017)
The electronic structure of stoichiometric tin dioxide (SnO2) is studied by probing its unoccupied states using the fine structure in the electron energy-loss spectra (EELS) at the oxygen-K (O-K) edge. The spectral measurements were performed both at room and at high temperatures (773 K) and compared to ab initio calculations carried out using the real-space multiple-scattering and linearized augmented-plane-wave methods. Important many-body effects are included via quasiparticle corrections calculated within the many-pole GW self-energy approximation. An additional energy-dependent damping is calculated to account for vibrational effects. Results from this paper demonstrated that quantitative agreement between theoretical and experimental spectra can be obtained when nonspherical potentials and quasiparticle self-energy effects are considered and vibrational broadening is included. Modifications of the electronic structure by single oxygen vacancies, both in the bulk and at the (110) surface, also are predicted. Our predictions support the use of O-K EELS as a probe of the defect structures in SnO2 surfaces and nanoparticles.